2011
DOI: 10.1021/ac200698q
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Organic Materials in Historic Oil Paintings Using Correlated Extractionless Surface-Enhanced Raman Scattering and Fluorescence Microscopy

Abstract: A novel spectroscopic approach, correlated surface-enhanced Raman scattering (SERS) and fluorescence microscopy, is used to identify organic materials in two 18th century oil paintings. The vibrational fingerprint of analyte molecules is revealed using SERS, and corresponding fluorescence measurements provide a probe of local environment as well as an inherent capability to verify material identification. Correlated SERS and fluorescence measurements are performed directly on single pigment particles obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 32 publications
7
57
0
Order By: Relevance
“…4A to account for the effect of fiber interaction on the indigo emission spectrum and it is in full agreement with the literature data for indigo. (Guineau, 1989) As can be seen, the spectrum of the red fiber matches exactly the reference sample (carmine) and with the results reported in the literature (Oakley et al, 2011), whereas there is a 23 nm blue shift when the blue fiber spectrum is compared with the solid indigo one, however, such difference almost disappear when the spectrum of a contemporary dyed wool fiber is used in the comparison (emission maximum at 712 nm for the archaeological fiber and 715 nm for the contemporary dyed one), thus confirming the assignment made by resonance Raman and evidencing the fact that the Raman microscope is effective as a microspectrofluorimeter in cultural heritage investigations.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…4A to account for the effect of fiber interaction on the indigo emission spectrum and it is in full agreement with the literature data for indigo. (Guineau, 1989) As can be seen, the spectrum of the red fiber matches exactly the reference sample (carmine) and with the results reported in the literature (Oakley et al, 2011), whereas there is a 23 nm blue shift when the blue fiber spectrum is compared with the solid indigo one, however, such difference almost disappear when the spectrum of a contemporary dyed wool fiber is used in the comparison (emission maximum at 712 nm for the archaeological fiber and 715 nm for the contemporary dyed one), thus confirming the assignment made by resonance Raman and evidencing the fact that the Raman microscope is effective as a microspectrofluorimeter in cultural heritage investigations.…”
Section: Resultssupporting
confidence: 85%
“…The importance of the emission spectroscopy in cultural heritage investigations has been shown in the literature (Claro et al, 2008, Oakley et al, 2011 but as far as the authors are aware a Raman microscope was not used before in dyes identification in fibers. Considering, however, that the potential of photoluminescence measurements by a Raman microscope was demonstrated several years ago (Dyer and Smith, 1995), the main point here is to emphasize that the proper choice of equipment and Rayleigh filters will allow the Raman and photoluminescence spectra to be obtained from the same spot and by the same instrument, what is certainly an excellent possibility in archaeometry which frequently deals with badly degraded (and luminescent) samples.…”
Section: Discussionmentioning
confidence: 99%
“…Various natural organic materials have been used in ancient artworks, such as oils, lipids, protein, polysaccharide, wax, resin, varnishes and protective materials. One of the most used natural organic materials is drying-oil as binding media in polychromic artworks in both eastern and western countries [1][2][3][4]. It is reported that the usually used drying-oils are linseed-oil, poppy-oil or walnut-oil in western artworks, while tungoil (also named wood oil or Chinese wood oil) is mainly used in eastern artworks [5], but they have similar main compositions of glyceride and C18 unsaturated fatty acids with 1, 2 or 3 double bonds.…”
Section: Introductionmentioning
confidence: 99%
“…But these techniques are commonly accompanied with very complicated preliminary scission of polymeric chain by hydrolysis in obtaining characteristic marked components [17]. Nevertheless, nuclear magnetic resonance (NMR) [3,18], infrared spectroscopy (IR) [19,20], Raman spectroscopy (RS) [4,21,22] and micro-fluorimetry [23] techniques are reported in the analysis of dry-oil, but they are actually inadequate in identifying the specific oil substances, since they are only effective in roughly distinguishing drying-oil from other binding media, such as polysaccharide [21], resin [21,22], wax [22] or protein-based materials [21,23]. Fortunately, pyrolysis coupled with gas chromatography-mass spectrometry (Py-GC/MS) technique, working by thermally cracking the macro-molecule materials into low-molecule compounds and followed by directly GC separating with MS detection, could overcome these shortages to provide a rapid and effective answer to the nature of organic materials [17,[24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The first extractionless non-hydrolysis study of organic dyes in oil paintings was reported by Oakley et al (2011), who employed colloidal pastes to examine red colorants in oil glazes from works belonging to the Colonial Williamsburg Foundation collection, i.e. Portrait of William Nelson (1748-50) by the earliest native-born American artist of European descent, Robert Feke, and Portrait of Isaac Barré (1766) by Sir Joshua Reynolds, a founder of the Royal Academy of Arts.…”
Section: Paintingsmentioning
confidence: 99%